Perspectivism and Social Cartography: contributions to comparative education - Jorge M. Gorostiaga (Universidade Federal do Rio Grande do Sul, 2017)
This article argues that a perspectivist approach provides a form of comparison (the analysis of similarities, differences and inter-relationships between different perspectives) that contributes as a valuable tool for the study of educational problems. In particular, it discusses methodological features of social cartography and how it falls within the debates of the field of comparative education. In addition, it illustrates its application to education policy problems from a comparative perspective in the Latin American context, focusing on a study that analyzed the intertextual debate on globalization and education reform in the region during the 1996-2008 period.